Strengthening small business management - Schabacker, Joseph Charles (Washington : [Small Business Administration; for sale by the Supt. of Docs., U.S. Govt. Print. Off., 1971)
This book was brought together here with the aim of presenting a meaningful philosophy of management in practice.
selections from the papers of L. T. White.
Includes bibliographical references.
hza 26/09/2018
Loans
Keywords: Small Business (manage)